Multicultural citizenship or citizenship in a multicultural polity . - Bennett, Fred. (University of Ottawa (Canada), 2001)
Citizenship in liberal democracies has, until recently, been theorized as conferring equal legal status on all citizens irrespective of their race, religion, ethnicity, culture or language. While much discrimination and unequal treatment existed in practice, the theory was that all citizens should be treated equally, exactly the same, regardless of their individual characteristics; the state should be neutral in dealing with its citizens. In recent years, political theorists such as Charles Taylor, Will Kymlicka, Yael Tamir, J. Raz, Iris Marion Young, and Anne Phillips have challenged both the practice and theory of the traditional view of citizenship. They argue that state neutrality has not been the case in actual practice; states discriminate in favour of dominant cultures. Furthermore the say such neutrality is, for a variety of reasons, impossible They also argue that it is not desirable even in theory. An individual's culture is essential to their being and deserves to be positively recognized by the state. This thesis argues that, while there are problems with the traditional view of a difference-blind citizenship and the idea of the neutral state, the philosophical arguments put forward by the critics are untenable. These arguments, and the political policies their implementation would entail, pose insurmountable problems for democratic deliberation and fail to take account of possible empirical results. The traditional view of citizenship and state neutrality can be rethought and implemented in what is called "the indifferent state"---a state which, while indifferent to its citizens' culture, religion etc., is not indifferent to the impact that these may have on the instantiation of such traditional liberal political values as equality and autonomy. The thesis concludes with three case studies which illustrate the differences in approach between the traditional view of citizenship, the view of the critics, and that of the indifferent state.
Keywords: Philosophy.